Sosialisasi Inovasi Pupuk Organik Cair (POC) Limbah Rumah Tangga dan Limbah Tanaman: Strategi Edukasi Lingkungan kepada Masyarakat - Kamila Widi Pratama; Febyulta Zanarani Pitaloka; Mayva Arum Ningtyas Hamengkubudi; Prasasti Dinar Rahmalia; Jonathan Rojaya Morales Sihaloho (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
Excessive use of inorganic fertilizers can cause soil quality degradation and environmental pollution. KWT Tunas Lestari Jaya in Sukoharjo Regency still uses inorganic fertilizer for the land at the KWT Tunas Lestari Jaya location because they don't understand how to process organic waste into liquid organic fertilizer. Abundant household and plant waste is not managed optimally, causing the accumulation and burning of waste which has a negative impact on the environment. The aim of this activity is to increase the knowledge and skills of KWT Tunas Lestari Jaya members in utilizing household organic waste into liquid organic fertilizer to reduce the impact of environmental pollution. The method used is training and counseling with a participatory lecture and discussion approach. The activity was carried out on April 27 2025 at KWT Tunas Lestari Jaya, Sukoharjo. The analysis technique uses descriptive evaluation based on four indicators: level of participant attendance, understanding of the material, application of skills, and relevance of the material to community needs. The results showed that the program was successful with an attendance rate of 100%, participants showed high enthusiasm, there was an increase in knowledge about the benefits and methods of making POC, participants were able to practice organic waste processing techniques using the fermentation method, and there was a change in mindset from burning waste to using organic waste as raw material for POC. This program has succeeded in empowering the community in managing organic waste and contributing to the creation of a cleaner and healthier environment.